Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

. If f(x) = 7x2 – 3x + 7, find f(2) + f(–1) + f(0).​

Sagot :

♪Answer :

»f(x) = 7x² - 3x + 7

  • find f(2) in f(x)

»f(2) = 7(2)² - 3(2) + 7

»f(2) = 7(4) - 6 + 7

»f(2) = 28 - 6 + 7

»f(2) = 29

  • find f(-1) in f(x)

»f(-1) = 7(-1)² - 3(-1) + 7

»f(-1) = 7(1) + 3 + 7

»f(-1) = 7 + 3 + 7

»f(-1) = 17

  • find f(0) in f(x)

»f(0) = 7(0)² - 3(0) + 7

»f(0) = 7(0) - 0 + 7

»f(0) = 0 - 0 + 7

»f(0) = 7

so, f(2) + f(-1) + f(0) is

  • 29 + 17 + 7
  • = 53
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.